Let it snow : a novel - Thayer, Nancy, 1943- (Ballantine Books, 2019)
"Christina Antonioni is preparing for the holidays at her Nantucket toy shop, unpacking last-minute shipments and decorating for her loyal Christmas shoppers. But when her Scrooge of a landlord, Oscar Bittlesman, raises her rent, it seems nearly impossible for Christina to continue business on the wharf. Even so, Christina hopes there is a warm heart underneath Oscar's steely exterior. When she bonds with Wink, his sweet, young granddaughter who frequents the shop, it becomes clear that perhaps he isn't so cold after all. And with the help of Wink's uncle, who happens to be a charming and very handsome bachelor, this may be the best Christmas any of them could have ever imagined. Nancy Thayer's enchanting Nantucket setting provides the perfect backdrop for this holiday love story"--